A Critique of Stephen Downes’ Article, “Learning Objects”: A Chinese Perspective - Lin, Fuhua Oscar (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2001)
This paper by Stephen Downes recommends a way of sharing online teaching/ course materials to accelerate course development and make education more cost-effective. His paper is a review of basic information about learning objects (LOs) and includes examples that illustrate such technical terms as XML and TML.